(untitled) (Research, Society and Development, 2020)
The objective is to analyze the procedures used by the nursing team in the prevention of hypothermia in the perioperative period in elective and emergency surgeries. This is a literature search with a qualitative approach carried out by the Integrative Review (IR) method, based on the data available in the Virtual Health Library, filtered in the period from 2015 to 2020, establishes a wide methodological interpellation regarding the reviews, inserting different types of studies expanding the understanding of the phenomenon studied. To search the databases, the following descriptors were listed: Perioperative nursing, general surgery, methods, hypothermia, elective surgical procedures, surgical centers. The descriptors were grouped in different ways using the Boolean operators AND and OR simultaneously aggregating the subjects. It was observed that there are passive and active methods of heating that can be used to control hypothermia in the perioperative period. Authors reaffirm the need for heating throughout the perioperative period, using materials (eg sheets and blankets) and keeping the patient’s skin surface as small as possible, as a passive method responsible for reducing 30% of heat loss. The researchers mention the use of active methods such as prevention and protection of the patient, with forced air system. These methods demonstrate significant efficacy in reducing hypothermia rates at the surgical site. There is a clear need for training professionals in the operating room, seeking a new model of preventive care that helps to reduce risk factors and possible damage caused to the patient.